EXPRESSION OF HSA-MIR-22-3P IN THE URINE OF PROSTATE CARCINOMA PATIENTS AS A NON-INVASIVE BIOMARKER - Prasetyo, Angga Dwi; Danarto, R.; Haryana, Sofia Mubarika; Astuti, Indwiani (BRIN Publishing (Penerbit BRIN), 2025)
Prostate carcinoma is one of the prostate diseases with the highest prevalence in men. Many factors cause the disease; some are androgen receptor disorder, mutation of genes, age, epigenetics, and environment. Currently, the detection of the disease is done by Prostate-Specific Antigen (PSA), Transurethral Resection of Prostate (TURP), and Digital Rectal Examination (DRE) tests; all of which are invasive to the patients. The microRNA that exists in urine exosomes can be used to detect non-invasive prostate carcinoma. Hsa-miR-22-3p with Gleason Score. This study aimed to examine the expression potential of Hsa-miR-22-3p in urine samples of prostate carcinoma exosomes as a non-invasive biomarker to determine the correlation between the expression of Hsa-miR-22-3p and the value of the Gleason Score. This study is of cross-sectional observational analysis. Urine samples were obtained from RSUP dr. Sardjito Yogyakarta dan RSUP dr. Soeradji Tirtonegoro. The exosome isolation was then carried out, followed by RNA isolation, cDNA synthesis, and quantification using qRT-PCR. Based on the result of the study, there was a decrease in the expression of Hsa-miR-22-3p by 6.6 times in prostate carcinoma; there was a significant difference between the samples of prostate carcinoma and healthy individuals (P = 0,031), and there was a correlation between the expression level of Hsa-miR-22-3p and the value of Gleason Score. Therefore, Hsa-miR-22-3p has the potential to be used as a biomarker for prostate carcinoma patients.